Terminus-driven retreat of a major southwest Greenland tidewater glacier during the early 19th century: insights from glacier reconstructions and numerical modelling - Lea, James M; Mair, Douglas W.F.; Nick, Faezeh M; Rea, Brice R; Weidick, Anker; Kjaer, Kurt H; Morlighem, Mathieu; Van As, Dirk; Schofield, J. Edward (Journal of Glaciology, 2014)
Tidewater glaciers in Greenland experienced widespread retreat during the last century. Information on their behaviour prior to this is often poorly constrained due to lack of observations, while determining the drivers prior to instrumental records is also problematic. Here we present a record of the dynamics of Kangiata Nunaata Sermia (KNS), southwest Greenland, from its Little Ice Age maximum (LIAmax) to 1859 – the period before continuous air temperature observations began at Nuuk in 1866. Using glacial geomorphology, historical accounts, photographs and GIS analyses, we provide evidence KNS was at its LIAmax by 1761, had retreated by ∼5 km by 1808 and a further 7 km by 1859. This predates retreat at Jakobshavn Isbrae by 43–113 years, demonstrating the asynchroneity of tidewater glacier terminus response following the LIA. We use a one-dimensional flowband model to determine the relative sensitivity of KNS to atmospheric and oceanic climate forcing. Results demonstrate that terminus forcing rather than surface mass balance drove the retreat. Modelled glacier sensitivity to submarine melt rates is also insufficient to explain the retreat observed. However, moderate increases in crevasse water depth, driving an increase in calving, are capable of causing terminus retreat of the observed magnitude and timing.